High occurrence of food insecurity in young people attending a youth mental health service in regional Australia. Issue 3 (7th July 2022) - Kent, Katherine; Murray, Sandra; Visentin, Denis; Mawer, Tamieka; McGowan, Courtney J.; Williams, Andrew D.; Hardcastle, Sibella; Bridgman, Heather
Abstract: Aim: Despite the relationship between food insecurity and poor mental health, food insecurity in young people attending mental health services in Australia remains understudied. This study aimed to determine the occurrence and predictors of food insecurity, and the relationship with dietary factors in young people attending a mental health service. Methods: A cross‐sectional online survey was conducted in a sample of young people (15–25 years) who attended a mental health service in Launceston, Australia. The survey utilised a single‐item food insecurity screening tool and eight demographic, health and service use questions. Five questions determined self‐reported intake of fruit, vegetables, breakfast, water, sugar‐sweetened beverages and takeaway foods. Binary logistic regression determined predictors of food insecurity. Cross‐tabulations determined differences in dietary intake according to food security. Results: Of survey respondents ( n  = 48; 68% female), 40% ( n  = 19) were food insecure. Respondents living out of home or in unstable accommodation were at significantly higher risk of food insecurity (odds ratio [OR]: 4.43; SE: 0.696; 95% CI: 1.13–17.34; p  = 0.032) compared to those living with their parents. Those receiving government financial assistance (OR: 5.00; SE: 0.676; 95% CI: 1.33–18.81; p  = 0.017) were also at significantly higher risk of food insecurity. Regardless of food security status, self‐reported intake of fruits, vegetables and breakfast were low, and respondents regularly consumed takeaway foods and sugar‐sweetened beverages. Conclusions: There was a high occurrence of food insecurity and poor dietary intake in young people attending a youth mental health service demonstrating that initiatives to support access to healthy food in this group should be a priority, with potential benefits for mental health outcomes.